Preparation method of jack fruit shell biomass hard carbon material for negative electrode of sodium ion battery
Through the preparation method of jackfruit shell biomass hard carbon material, the problem of insufficient performance of the negative electrode material in sodium ion batteries is solved, and high specific capacity and excellent circulation performance are achieved, which is suitable for industrial applications of sodium ion batteries.
Patent Information
- Application Number
- CN202411228554.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-03
AI Technical Summary
There is a lack of high-performance negative electrode materials in sodium ion batteries. Graphite materials have limited the development of sodium ion batteries due to their thermodynamic instability and low storage capacity. The existing biomass hard carbon materials have high cost and poor cycle stability, which affect battery performance.
The preparation method of jackfruit shell biomass hard carbon material includes ash washing, drying, crushing, drying of alkali liquid, low-temperature pre-carbonization, acid washing, and high-temperature carbonization again to form a negative electrode with high specific capacity and excellent circulation performance Material.
The prepared jackfruit shell biohard carbon material significantly improves the first Coulomb efficiency and circulation performance of sodium ion batteries, is cheap, has an environmentally friendly process, and is suitable for large-scale industrial production.
Smart Images

Figure CN119118098A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a jackfruit shell biomass hard carbon material for a negative electrode of a sodium ion battery. Background Art
[0002] Sodium-ion batteries and lithium-ion batteries have similar working principles, and sodium resources are abundant, low-cost, and have excellent low-temperature performance and cycle life. They have broad application prospects in large-scale energy storage, power batteries, drones and other fields. At present, the technologies of positive electrode materials, diaphragms, electrolytes and other technologies of sodium-ion batteries are relatively mature, but the lack of high-performance negative electrode materials has limited the industrial development of sodium-ion batteries to a certain extent. The radius of sodium ions (about 0.1nm) is much larger than that of lithium ions (about 0.06nm). In theory, the graphite materials used in lithium-ion batteries are not conducive to the deintercalation of sodium ions due to their small interlayer spacing, which will greatly reduce the storage capacity of sodium ions in graphite. Moreover, stable intercalation compounds cannot be formed between sodium and graphite. This thermodynamic instability makes graphite difficult to use as the negative electrode material of sodium-ion batteries, further affecting the development of sodium-ion battery technology.
[0003] Different from the lithium storage mechanism of graphite, the sodium storage mechanism of hard carbon is more complicated, mainly including intercalation reaction mechanism, alloying reaction mechanism and conversion reaction mechanism. Sodium ions can be stored in three locations in hard carbon: the edges and defects of the hard carbon surface, the gaps between graphite layers, and the micropores formed between randomly oriented graphite. At present, coconut shell biomass materials and phenolic resins are used as hard carbon precursors. Although they can bring stable structures, they still have problems such as poor cycle stability, high cost and poor rate performance, which in turn affect the performance of the battery. Therefore, it is urgent to find a suitable negative electrode material to solve the problems of low capacity retention and low coulomb efficiency of sodium ion batteries. Summary of the invention
[0004] In view of the defects of the prior art, the present invention prepares a jackfruit shell bio-hard carbon material for the negative electrode of a sodium ion battery. The preparation method has a simple process flow, low cost, and is environmentally friendly. The sodium ion battery assembled from the prepared jackfruit shell bio-hard carbon material has the advantages of high specific capacity, significantly improved first coulombic efficiency, and excellent cycle performance.
[0005] In order to achieve the above purpose, the present invention solves the technical problem by adopting the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a jackfruit shell bio-hard carbon material for a sodium ion battery negative electrode, comprising the following steps:
[0007] S1. Washing, drying, crushing, soaking in lye and drying the jackfruit shell to obtain a precursor;
[0008] S2. Pre-carbonizing and etching the precursor at low temperature and without oxygen to obtain pyrolytic carbon;
[0009] S3. The pyrolytic carbon is immersed in an alkali solution and an acid solution, washed to neutrality, and dried to obtain an intermediate;
[0010] S4. The intermediate is subjected to secondary oxygen-free high-temperature carbonization to obtain the final product, i.e., jackfruit shell biomass hard carbon.
[0011] Preferably, the drying temperature is 50-120° C., and the drying time is 12-72 hours.
[0012] Preferably, in step S1, the alkali solution is one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, and aqueous ammonia, and the concentration is 0.2-5 mol / L.
[0013] Preferably, in step S1, the alkali solution is prepared by soaking the crushed jackfruit shells in the alkali solution, and the mass proportion of the jackfruit shells in the alkali solution is 10-50%.
[0014] Preferably, in step S2, the low-temperature pre-carbonization is carried out in an inert gas, the low-temperature pre-carbonization temperature is 400-600°C, the time is 2-7h, and the heating rate is 2-10°C / min.
[0015] Preferably, in step S3, the acid solution is one or more of sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid, etc., with a concentration of 3-6 mol / L.
[0016] Preferably, in step S3, the alkali solution is one or more solutions of sodium hydroxide, potassium hydroxide, barium hydroxide, ammonia water, etc., with a concentration of 3-6 mol / L.
[0017] Preferably, in step S4, the high-temperature carbonization is carried out in an inert gas, the high-temperature carbonization temperature is 900-1500°C, the time is 5-12h, and the heating rate is 5-15°C / min.
[0018] On the one hand, the present invention provides a jackfruit shell bio-hard carbon material prepared by the preparation method.
[0019] On the other hand, the present invention also provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a casing, wherein the negative electrode sheet comprises the jackfruit shell bio-hard carbon material according to claim 9.
[0020] The present invention adopts one or more alkaline solutions containing sodium hydroxide, barium hydroxide and potassium hydroxide on the basis of low-temperature carbonization. The sodium hydroxide or potassium hydroxide can react with impurities doped in the original biomass to improve the purity of the hard carbon material prepared subsequently, and can act on the acidic functional groups of the material to generate redox reactions, which can further etch the surface of the material, increase the pore and pore wall structure, and swell the carbon skeleton of the pore, thereby increasing the pore diameter, improving the pore structure of the hard carbon material, and improving the specific surface area and adsorption performance. At the same time, the alkali also generates acid-base neutralization reactions with the acidic functional groups in the jackfruit shell to cause certain corrosion on the surface, thereby increasing the pore and pore wall structure, and the alkali can react with the graphite oxide groups in the biomass carbon at high temperature, causing the carbon skeleton to be destroyed, forming new functional groups, further increasing the density and activity of the pore and pore wall, and improving the adsorption performance of the material so that it can accommodate more sodium ions.
[0021] In addition, low-temperature pre-carbonization can also reduce the release of volatile substances in biomass raw materials, retaining more carbon elements in the solid product, thereby increasing the yield and purity of hard carbon; after that, it is soaked in alkali and acid to remove impurities, and finally subjected to high-temperature carbonization treatment to obtain high-performance jackfruit shell-based hard carbon negative electrode materials.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention uses jackfruit shell as a raw material, and prepares a biological hard carbon material that can be used for the negative electrode of a sodium ion battery after alkali solution soaking, low-temperature pre-carbonization, alkali solution soaking, acid solution soaking, and high-temperature carbonization. The biological hard carbon material has a large number of lamellar structures and honeycomb network structures, can enable sodium ions to be effectively deintercalated at the negative electrode, has good electrochemical properties, provides a new idea for the research and development of sodium ion battery technology, and has broad application prospects.
[0024] The preparation method of the invention is green and environmentally friendly, has simple operation, can be industrially produced on a large scale, uses jackfruit shell as a raw material, has abundant source, low cost, and is conducive to sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the implementation mode will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a scanning electron microscope image of the intermediate treated with sodium hydroxide to form pores in Example 1 at a magnification of 5000 times.
[0027] Figure 2This is a scanning electron microscope image of the intermediate treated with sodium hydroxide to form pores in Example 1 at a magnification of 10,000 times.
[0028] Figure 3 This is a scanning electron microscope image of the intermediate of comparative example 1 without pore-forming treatment at a magnification of 5000 times.
[0029] Figure 4 This is a scanning electron microscope image of the intermediate of comparative example 1 without pore-forming treatment at a magnification of 10,000 times.
[0030] Figure 5 This is a cycle curve diagram of a sodium ion battery prepared from the jackfruit shell-based hard carbon negative electrode material after sodium hydroxide pore-forming treatment in Example 1.
[0031] Figure 6 This is a battery cycle curve of sodium ions prepared from the jackfruit shell-based hard carbon negative electrode material without pore-forming treatment in Example 1.
[0032] Figure 7 It is a charge and discharge curve diagram of the first three cycles of a sodium ion battery. In the diagram, A is a sodium ion battery prepared from a jackfruit shell-based hard carbon negative electrode material after a pore-forming treatment with sodium hydroxide in Example 1; B is a sodium ion battery prepared from a jackfruit shell-based hard carbon negative electrode material after a pore-forming treatment with sodium hydroxide in Comparative Example 1. DETAILED DESCRIPTION
[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0035] Example 1
[0036] A method for preparing a jackfruit shell biomass hard carbon material, the preparation method specifically comprising the following steps:
[0037] 1. Wash the jackfruit shell with deionized water, cut it into small pieces, shake it in an ultrasonic machine for 30 minutes, rinse it with deionized water, dry it to constant weight, and grind it into powder with a wall breaking machine to obtain a jackfruit shell powder raw material.
[0038] 2. Put the above-mentioned jackfruit shell powdered raw material into a beaker, add deionized water to cover the sample and place it in an 80℃ oil bath for 2 hours, then transfer it to a 1mol / L sodium hydroxide solution until it is completely immersed, where the sample accounts for 30% of the alkaline solution. After stirring and soaking at 60℃ for 2 hours, put it into a blast drying oven at 60℃ to dry the water to obtain a precursor uniformly mixed with sodium hydroxide.
[0039] 3. Transfer the precursor into a nitrogen-filled tubular furnace and heat it at 550°C for 5 hours at a rate of 2°C / min to obtain pre-pyrolysis carbon.
[0040] 4. Grind the pre-pyrolyzed carbon into powder, pass through a 1200 mesh sieve, soak in a 3 mol / L sodium hydroxide solution with stirring for 12 hours, wash until neutral, transfer to a 3 mol / L hydrochloric acid solution with stirring for 12 hours, and then wash until neutral to obtain an intermediate.
[0041] 5. Transfer the intermediate into a tubular furnace filled with nitrogen and heat the temperature to 1300°C at 10°C / min and keep it for 10 hours to obtain the jackfruit shell bio-hard carbon negative electrode material.
[0042] Example 2
[0043] A method for preparing a jackfruit shell biomass hard carbon material, the preparation method specifically comprising the following steps:
[0044] 1. Wash the jackfruit shell with deionized water, cut it into small pieces, shake it in an ultrasonic machine for 30 minutes, rinse it with deionized water, dry it to constant weight, and grind it into powder with a wall breaking machine to obtain a jackfruit shell powder raw material.
[0045] 2. Put the above-mentioned jackfruit shell powdered raw material into a beaker, add deionized water to cover the sample and place it in an 80℃ oil bath for 2 hours, then transfer it to 1mol / L sodium hydroxide until it is completely immersed, where the sample accounts for 30% of the mass of the alkaline solution. After stirring and soaking at 60℃ for 2 hours, put it into a blast drying oven at 60℃ to dry the water to obtain a precursor uniformly mixed with sodium hydroxide.
[0046] 3. Transfer the precursor into a nitrogen-filled tubular furnace and heat it at 400°C for 7 hours at a rate of 2°C / min to obtain pre-pyrolysis carbon.
[0047] 4. Grind the pre-pyrolyzed carbon into powder, pass through a 1200 mesh sieve, soak in a 3 mol / L sodium hydroxide solution with stirring for 12 hours, wash until neutral, transfer to a 3 mol / L hydrochloric acid solution with stirring for 12 hours, and then wash until neutral to obtain an intermediate.
[0048] 5. Transfer the intermediate into a tubular furnace filled with nitrogen and heat the temperature to 1500°C at 10°C / min and keep it for 5 hours to obtain the jackfruit shell bio-hard carbon negative electrode material.
[0049] Example 3
[0050] A method for preparing a jackfruit shell biomass hard carbon material, the preparation method specifically comprising the following steps:
[0051] 1. Wash the jackfruit shell with deionized water, cut it into small pieces, shake it in an ultrasonic machine for 30 minutes, rinse it with deionized water, dry it to constant weight, and grind it into powder with a wall breaking machine to obtain a jackfruit shell powder raw material.
[0052] 2. Put the above-mentioned jackfruit shell powdered raw material into a beaker, add deionized water to cover the sample and place it in an 80℃ oil bath for 2 hours, then transfer it to a 2mol / L potassium hydroxide solution until it is completely immersed, where the sample accounts for 50% of the mass of the alkaline solution. After stirring and soaking at 60℃ for 2 hours, put it into a blast drying oven at 60℃ to dry the water to obtain a precursor uniformly mixed with potassium hydroxide.
[0053] 3. Transfer the precursor into a nitrogen-filled tubular furnace and heat it at a rate of 10°C / min, and keep it at 600°C for 2 hours to obtain pre-pyrolysis carbon.
[0054] 4. Grind the pre-pyrolyzed carbon into powder, pass through a 1200 mesh sieve, soak in a 3 mol / L potassium hydroxide solution with stirring for 12 hours, wash until neutral, transfer to a 3 mol / L hydrochloric acid solution with stirring for 12 hours, and then wash until neutral to obtain an intermediate.
[0055] 5. The intermediate was transferred into a tubular furnace filled with nitrogen and heated to 900°C at 10°C / min and kept warm for 12 hours to obtain the jackfruit shell bio-hard carbon negative electrode material.
[0056] Comparative Example 1
[0057] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 is not etched with an alkaline solution, and the other aspects are the same.
[0058] 1. Wash the jackfruit shell with deionized water, cut it into small pieces, shake it in an ultrasonic machine for 30 minutes, rinse it with deionized water and dry it, and grind it into powder with a wall breaking machine to obtain a jackfruit shell powder raw material.
[0059] 2. Place the above-mentioned jackfruit shell powdered raw material in a 500-1000 mL beaker, add deionized water to cover the sample and place it in an 80° C. oil bath to keep warm for 2 hours, then place it in a forced air drying oven at 60° C. to dry it to obtain a precursor.
[0060] 3. Transfer the precursor into a nitrogen-filled tubular furnace and heat it at 550°C for 5 hours at a rate of 2°C / min to obtain pre-pyrolysis carbon.
[0061] 4. Grind the pre-pyrolyzed carbon into powder, pass through a 1200 mesh sieve, soak in a 3 mol / L sodium hydroxide solution with stirring for 12 hours, wash until neutral, transfer to a 3 mol / L hydrochloric acid solution with stirring for 12 hours, and then wash until neutral to obtain an intermediate.
[0062] 5. Transfer the intermediate into a tubular furnace filled with nitrogen and heat the temperature to 1300°C at 10°C / min and keep it for 10 hours to obtain the jackfruit shell bio-hard carbon negative electrode material.
[0063] Test Example 1
[0064] 1. The surface morphology of the jackfruit shell bio-hard carbon negative electrode material prepared in Example 1 and Comparative Example 1 was characterized by scanning electron microscopy.
[0065] Depend on Figure 1-4 It can be seen that the jackfruit shell bio-hard carbon negative electrode material prepared in Example 1 has a large number of obvious lamellar structures and honeycomb network structures, which are more conducive to the storage of sodium ions; while the jackfruit shell bio-hard carbon negative electrode material prepared in Comparative Example 1 without treatment with alkaline mixed solution has a similarly small particle size, but there is no obvious layered structure and etched defective pore structure on the surface.
[0066] 2. Electrochemical performance test:
[0067] 420 mg of the biomass hard carbon material prepared above and 20 mg of conductive carbon black were weighed and ground in an agate mortar for 20 min, then added to a solution mixed with 40 mg of PVDF and 400 mg of NMP, and stirred for 10 h to form a uniform mixture. The mixture was then evenly applied on a copper foil with a thickness of 200 μm, placed in an oven at 60°C and dried for 24 h, and then made into a disc electrode with a diameter of 12 mm using a slicer. The electrode was used as the negative electrode, a glass fiber (Whitman, GF / D) disc was used as a battery separator, metallic sodium was used as a counter electrode and a reference electrode, and a solution of 1 mol / L sodium hexafluorophosphate (NaPF6) dissolved in ethylene carbonate (EC): dimethyl carbonate (DMC) = 1:1 plus 5% wt fluoroethylene carbonate was used as an electrolyte. The sodium ion battery was assembled in a glove box filled with high-purity argon according to the structure of a CR2032 standard button cell.
[0068] The assembled batteries were subjected to cyclic charge and discharge tests on the Xinwei battery testing equipment, with the current density set to 0.2A / g.
[0069] Depend on Figure 5-6 It can be seen that the jackfruit shell bio-hard carbon negative electrode material of Example 1 has good cycle stability and has a higher capacity at a current density of 0.2A / g; while the jackfruit shell bio-hard carbon negative electrode material of Comparative Example 1 has average cycle stability, and its first efficiency is much lower, and its capacity is lower at a current density of 0.2A / g.
[0070] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a jackfruit shell bio-hard carbon material for a sodium ion battery negative electrode, characterized in that: The following steps are involved: S1. Washing, drying, crushing, soaking in lye and drying the jackfruit shell to obtain a precursor; S2. Pre-carbonizing and etching the precursor at low temperature and without oxygen to obtain pyrolytic carbon; S3. The pyrolytic carbon is immersed in an alkali solution and an acid solution, washed to neutrality, and dried to obtain an intermediate; S4. The intermediate is subjected to secondary oxygen-free high-temperature carbonization to obtain the final product, i.e., jackfruit shell biomass hard carbon.
2. The preparation method according to claim 1, characterized in that: In step S1, the drying temperature is 50-120°C, and the drying time is 12-72 hours.
3. The preparation method according to claim 1, characterized in that: In step S1, the alkali solution is one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, and ammonia water, and the concentration is 0.2-5 mol / L.
4. The preparation method according to claim 1, characterized in that: In step S1, the alkali solution is prepared by soaking the crushed jackfruit shells in the alkali solution, wherein the mass proportion of the jackfruit shells in the alkali solution is 10-50%.
5. The preparation method according to claim 1, characterized in that: In step S2, the low-temperature pre-carbonization is carried out in an inert gas, the low-temperature pre-carbonization temperature is 400-600°C, the time is 2-7h, and the heating rate is 2-10°C / min.
6. The preparation method according to claim 1, characterized in that: In step S3, the acid solution is one or more of sulfuric acid, hydrochloric acid, nitric acid, hydrofluoric acid, etc., with a concentration of 1-6 mol / L.
7. The preparation method according to claim 1, characterized in that: In step S3, the alkali solution is one or more solutions of sodium hydroxide, potassium hydroxide, barium hydroxide, ammonia water, etc., with a concentration of 1-6 mol / L.
8. The preparation method according to claim 1, characterized in that: In step S4, the high-temperature carbonization is carried out in an inert gas at a temperature of 900-1500°C, a time of 5-12h, and a heating rate of 5-15°C / min.
9. Jackfruit shell biological hard carbon material prepared by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and a shell, wherein the negative electrode sheet comprises the jackfruit shell bio-hard carbon material according to claim 9.
Citation Information
Patent Citations
A preparation method of biomass hard carbon material for negative electrode of sodium ion battery
CN109004199A
Waste biomass kernel derived hard carbon material as well as preparation method and application thereof
CN115863634A
Preparation method of sodium ion battery negative electrode material
CN116581289A
High-rate biomass-based hard carbon negative electrode material and preparation method thereof
CN117963885A
Sodium-ion battery negative electrode biomass hard carbon material, preparation method and sodium-ion battery
CN118529711A
